2014
DOI: 10.1371/journal.pone.0094339
|View full text |Cite
|
Sign up to set email alerts
|

Beliefs about the Minds of Others Influence How We Process Sensory Information

Abstract: Attending where others gaze is one of the most fundamental mechanisms of social cognition. The present study is the first to examine the impact of the attribution of mind to others on gaze-guided attentional orienting and its ERP correlates. Using a paradigm in which attention was guided to a location by the gaze of a centrally presented face, we manipulated participants' beliefs about the gazer: gaze behavior was believed to result either from operations of a mind or from a machine. In Experiment 1, beliefs w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

27
177
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 169 publications
(208 citation statements)
references
References 43 publications
27
177
4
Order By: Relevance
“…We found that the N170 -an early occipitotemporal brain response to 114 visual information -was larger in response to gaze shifts in the group who believed the 115 virtual character was human-controlled (see Wykowska et al, 2014 for similar findings). We 116 also found that the P350 -a later response measured over centro-parietal sites -was sensitive 117 to joint attention success only in the group who believed that the virtual character was 118 human-controlled.…”
Section: States? 81supporting
confidence: 57%
“…We found that the N170 -an early occipitotemporal brain response to 114 visual information -was larger in response to gaze shifts in the group who believed the 115 virtual character was human-controlled (see Wykowska et al, 2014 for similar findings). We 116 also found that the P350 -a later response measured over centro-parietal sites -was sensitive 117 to joint attention success only in the group who believed that the virtual character was 118 human-controlled.…”
Section: States? 81supporting
confidence: 57%
“…According to Wykowska et al [6] an intentional stance is required before people can attribute mental states to agents, and it was shown that beliefs about agency affect the effectiveness of a gaze cue [4,6]. The effects of gaze timing on the onset of imitation in our study are much larger than those observed using a gaze cueing paradigm, which is about 15 ms [4].…”
Section: Discussioncontrasting
confidence: 61%
“…But being able to extract the goal of a robot's movement is hardly sufficient to claim that people treat the robot as a 'social agent' rather than a machine. To attribute mental states to (artificial) agents requires an intentional stance [6]. ToM can be regarded as the fundamental link for achieving successful social interaction (in HHI), which ST cannot fully explain [3,19].…”
Section: Social Gaze Cuesmentioning
confidence: 99%
See 1 more Smart Citation
“…Indeed, interacting with agents assumed to be "intentional" is fundamentally different from interacting with non-intentional objects [6]. For example, it has been shown that intentionality-attribution and underlying mentalizing influence sensory processing to become "social perception", an altered understanding of each other's actions [19,14], which is also known as an "intentional stance" [4]. Clearly, these processes play an important role not only in solitary observation events, in which they have been studied mostly so far, but even more so in continuous online interaction [8,13].…”
Section: Introductionmentioning
confidence: 99%